Optimization of Oxidative Desulfurization Reaction with Fe2O3 Catalyst Supported on Graphene Using Box-Behnken Experimental Method - Hameed Hussein Alwan; Ammar Ali Ali; Hasan F. Makki (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
In this study, the catalyst activity of Fe2O3 supported on Graphene for Iraqi gas oil oxidation desulfurization (ODS) by hydrogen peroxide (H2O2) was investigated. The prepared catalyst was synthesized by wet impregnation for ferric nitrate as a Fe2O3 precursor while Graphene represented as catalyst support. The synthesized catalyst was characterized by XRD, FTIR, and EDS analysis. The experiments were designed according to three-level for three variables by Box-Behnken experimental design; Stirring time, catalyst dosage and temperature while the sulfur removal efficiency acts as experiment response. Catalyst activity was studied by ODS reaction for Iraqi gas oil (sulfur content 9400 ppm) at temperature range (40-60 ºC), stirring time (160-240 minutes) and catalyst dosage (0.5-2.5 g), the results show maximum sulfur removal efficiency 90% at stirring time, catalyst dosage and temperature 240 min, 1.5 g, and 60 ºC, respectively. ANOVA analysis shows the important effect of each independent variable on sulfur removal efficiency (response) as following influential order; stirring time, reaction temperature and catalyst dosage. Kinetics calculation showed that the ODS reaction obeys pseudo first-order reaction with reaction rate constant equal 1.0837, 1.5893, and 2.5053 at temperature 40, 50, and 60 ºC, respectively, while activation energy equal 36.26 kJ/mol. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).